Education and energy: in direction to sustainable development - Silva, Fábio Esteves; Sena, Galeno José; Fiscarelli, Silvio Henrique (Revista Ciências Exatas, 2008)
The use of energy in general not always it is understood by the common citizen and the problems related to the theme are camouflaged by this knowledge lack. To improve the teaching process in energy becomes of crucial importance in the current context, mainly in countries in development. Allied to this improvement, the use of new technologies of information appears as a true challenge in the most several means and academic levels. The search for the diversification of the national energy head office should consider the subject of the Renewable Energy, pointed as a probable one, and fort runs for office, the partial substitution of the employed resources in the electric power generation. This work defends the idea that only with the implantation of reforms in the teaching is that will get to reach a larger number of people than with knowledge will be multiplayers of the rational use of energy, providing a better use of the available energy resources, turning like this them, accessible to all with smaller environmental impacts.